2013
DOI: 10.1089/ten.tea.2011.0725
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Surface Chemical Treatment of Electrospun Poly(l-Lactide) Microfibrous Scaffolds for Enhanced Cell Adhesion, Growth, and Infiltration

Abstract: Poly(l-lactide) (PLLA) microfibrous scaffolds produced by electrospinning were treated with mild Ar or Ar-NH 3 /H 2 plasmas to enhance cell attachment, growth, and infiltration. Goniometry, atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS) measurements were used to evaluate the modification of the scaffold surface chemistry by plasma treatment. AFM and XPS measurements showed that both plasma treatments increased the hydrophilicity without affecting the integrity of the fibrous structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 29 publications
3
80
0
Order By: Relevance
“…The visualization of the scaffold cross sections by fluorescent microscopy after DAPI staining revealed that both plasma treatments are efficient in improving BAEC infiltration into the scaffolds. In vivo subcutaneous implantation of PLLA scaffolds under rat skin also enhanced the cellular infiltration when plasmatreated [161]. Atmospheric pressure plasma was also employed to activate PLLA fibers and similar surface analysis techniques and cell tests were conducted.…”
Section: Plla Fibersmentioning
confidence: 99%
“…The visualization of the scaffold cross sections by fluorescent microscopy after DAPI staining revealed that both plasma treatments are efficient in improving BAEC infiltration into the scaffolds. In vivo subcutaneous implantation of PLLA scaffolds under rat skin also enhanced the cellular infiltration when plasmatreated [161]. Atmospheric pressure plasma was also employed to activate PLLA fibers and similar surface analysis techniques and cell tests were conducted.…”
Section: Plla Fibersmentioning
confidence: 99%
“…Whereas the smooth muscle cells showed no significant increase in proliferation in-vitro, in-vivo tests revealed that cells were able to penetrate the scaffolds more efficiently and at higher densities, mainly due to the increased wettability. Cheng et al [85] found similar results in-vivo for their Ar-/NH 3 -treated PLA scaffolds -indicating that for cell infiltration, wettability is most likely the critical factor. When it comes to mineralization, Yang et al [76] found similar results compared to Yildirim et al [86] in the rapid prototyping section: improved mineralization within the first few hours after immersion of Ar plasma-treated scaffolds into simulated body fluid (SBF) solution.…”
Section: Electrospinningmentioning
confidence: 71%
“…The scaffolds structure and pattern (PC, PCO, PCOP, and PCOPG) along with their fiber diameters are presented in Figure 2(a-e). 43 The surfaces of electrospun poly(L-lactide) microfibrous scaffolds did not change after plasma treatment in their study, but the surface of the chemical altered with plasma modification has changed. Interconnected pores and network microstructure have been formed throughout the electrospinning technique, according to the SEM images.…”
Section: Morphology Observationmentioning
confidence: 86%